Efeito China, oportunidade ou ameaça? Um estudo do caso da Companhia Vale do Rio Doce - Mangabeira, Rubens Farias de Azevedo (2007)
The present study discusses the growth of Brazilian Companhia Vale do Rio Doce (Vale) and the role China has played on this fact. China has yearly grown at a 9.5% rate, for over two decades now, this process being mainly sustained by the high state investment in equipment and facilities, which has demanded steel for infrastructure and industrial settings. With the steel production increase, and China becoming the world's largest producer and consumer, the demand for iron ore has also increased by 50%, from 1996 to 2005. Mining companies have been investing in production expansion so as to attend to customers. China, once again, stands out, having overcome Japan as world's greatest consumer and responded for nearly half of world's consumption in 2005. In this context, the objective of this work is to synthesize and evaluate strategies adopted by Vale to use the favorable scenario to the mining companies in favor of its own growth, the results reached and the China influence on them.